2015
DOI: 10.1186/1471-2482-15-14
|View full text |Cite
|
Sign up to set email alerts
|

Sciatic nerve course in adult patients with unilateral developmental dysplasia of the hip: implications for hip surgery

Abstract: BackgroundSciatic nerve injury is a disastrous adverse complication of surgery and can cause debilitating pain, functional impairment and poor quality of life. Patients with developmental dysplasia of the hip (DDH) have a high incidence of sciatic nerve injury after total hip arthroplasty (THA). A better understanding of the course of the sciatic nerve in patients with DDH may help minimise the risk of sciatic nerve injury after THA.MethodsA total of 35 adult patients with unilateral DDH were enrolled in this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 28 publications
(27 reference statements)
1
16
1
Order By: Relevance
“…Supporting this, to reduce the risk of nerve kinking at the fragment edge, flexion of the hip is recommended. In contrast to these studies, the present study found higher distances from the nerve to the bone at the neutral position compared to [8][9][10] N abext 10 ± 1 [10][11] flexion or neutral/abduction/external rotation. This is probably due to the fact that the distance from the nerve to the bone was measured in this CT study rather than the tension of the nerve in a cadaver.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Supporting this, to reduce the risk of nerve kinking at the fragment edge, flexion of the hip is recommended. In contrast to these studies, the present study found higher distances from the nerve to the bone at the neutral position compared to [8][9][10] N abext 10 ± 1 [10][11] flexion or neutral/abduction/external rotation. This is probably due to the fact that the distance from the nerve to the bone was measured in this CT study rather than the tension of the nerve in a cadaver.…”
Section: Discussioncontrasting
confidence: 99%
“…We only included male adult participants with healthy hips. However, developmental hip dysplasia is mostly seen in female patients and patients with developmental hip dysplasia have altered anatomy also affecting the bone to nerve relationship and/or distance [9,10]. A second CT was used to measure the distances, which may not be as precise as with MR for identifying soft tissue but is superior to it for bone examination.…”
Section: Discussionmentioning
confidence: 99%
“…The distance between the SN and the lesser trochanter tip was 21 ± 1 mm in the present study, similar to the results of a study of computed tomography (CT) images conducted by Liu et al, 8 reporting a distance of 21.2 ± 5 mm. The authors noted that CT analysis was performed with the pelvis in the neutral position, with the lower limb placed in internal rotation.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, the links between chronicity and dosage of GC therapy can lead to increased risk of fractures. 20 …”
Section: Discussionmentioning
confidence: 99%